Analisis Framing Branderpreneurship pada BANK DKI: Inovasi dan Keterlibatan dalam Platform Keuangan Digital - Dwi Novialetta, Lola; Agustini, Prima (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze how BANK DKI's branderpreneurship strategy is framed in presenting innovation and enhancing user engagement through digital financial platforms. A framing analysis approach is employed to identify how BANK DKI constructs its narrative, image, and public communication in response to the digital transformation within the banking sector. Data were collected through digital media documentation, communication campaigns, and official publications from BANK DKI. The findings indicate that BANK DKI adopts an innovative framework emphasizing inclusivity, service digitalization, and collaboration with local communities. This framing successfully reinforces the institution’s image as a pioneer of digital finance that is adaptive to the evolving needs of urban society. The study recommends that effective branderpreneurship requires a consistent, value-based narrative that is responsive to digital dynamics.